Improving Treatment Outcome in Children With Obesity by an Online Self-Control Training: A Randomized Controlled Trial - Vermeiren, Eline; Naets, Tiffany; Van Eyck, Annelies; Vervoort, Leentje; Ysebaert, Marijke; Baeck, Nele; De Guchtenaere, Ann; Van Helvoirt, Maria; Tanghe, Ann; Bruyndonckx, Luc; De Winter, Benedicte Y.; Verhulst, Stijn L.; et al. (Frontiers in Pediatrics, 2021)
BACKGROUND Currently available treatment programs for children with obesity only have modest long-term results, which is (at least partially) due to the poorer self-control observed within this population. The present trial aimed to determine whether an online self-control training, training inhibition and redirecting attentional bias, can improve the short- and long-term treatment outcome of (in- or outpatient) child obesity treatment programs. METHODS In this double-blind multi-center randomized controlled trial, participants aged 8-18 years with obesity were allocated in a 1:1 ratio to receive an online self-control or sham training added to their in- or outpatient multidisciplinary obesity treatment program. The primary endpoint was BMI SDS. Data were analyzed by linear mixed models and the main interactions of interest were randomization by time and randomization by number of sessions, as the latter was cumulatively expressed and therefore represents the effect of increasing doses of the self-control training over time. RESULTS One hundred forty-four inpatient (mean age 14.3 +- 2.2 years, BMI 2.7 +- 0.4 SDS, 42% male) and 115 outpatient children (mean age 11.9 +- 2.1 years, BMI 2.4 +- 0.4 SDS, 45% male) were included. Children’s BMI lowered significantly during treatment in both the in- and outpatient treatment centers, p<0.001. In a mixed model with BMI as dependent variable, randomization by time was non-significant, but the number of self-control trainings (randomization*number of sessions) interacted significantly with setting and with age (p=0.002 and p=0.047), indicating a potential effect in younger inpatient residents. Indeed, a subgroup analysis on 22 inpatient children of 8-12 years found a benefit of the number of self-control trainings on BMI (p=0.026). CONCLUSIONS The present trial found no benefit of the self-control training in the entire study population, however a subgroup of young, inpatient participants potentially benefited. The trial was registered at https://www.isrctn.com as ISRCTN14722584.